2014
DOI: 10.1039/c3ta14959e
|View full text |Cite
|
Sign up to set email alerts
|

High-performance supercapacitor electrode based on a polyaniline nanofibers/3D graphene framework as an efficient charge transporter

Abstract: The distinctive architecture of the PANI/3D graphene electrode enhances its supercapacitive performance (1024 F g¬1), the lightweight and porous conducting foam provides “freeways” for fast charge transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
102
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(110 citation statements)
references
References 36 publications
6
102
2
Order By: Relevance
“…A maximum specific capacitance of the PANI/3D graphene electrode has been documented as high as $ 1024 F g À 1 at 10 mV s À 1 scan rate, and $ 1002 F g À 1 at 1 mA cm À 2 respectively, in 1 M H 2 SO 4 [85]. The high surface area offered by the conducting, porous 3D graphene framework stimulates effective utilisation of the deposited PANI and improves electrochemical charge transport and storage.…”
Section: D Graphene-based Architectures As Scaffolds In Supercapacitorsmentioning
confidence: 98%
See 1 more Smart Citation
“…A maximum specific capacitance of the PANI/3D graphene electrode has been documented as high as $ 1024 F g À 1 at 10 mV s À 1 scan rate, and $ 1002 F g À 1 at 1 mA cm À 2 respectively, in 1 M H 2 SO 4 [85]. The high surface area offered by the conducting, porous 3D graphene framework stimulates effective utilisation of the deposited PANI and improves electrochemical charge transport and storage.…”
Section: D Graphene-based Architectures As Scaffolds In Supercapacitorsmentioning
confidence: 98%
“…The high surface area offered by the conducting, porous 3D graphene framework stimulates effective utilisation of the deposited PANI and improves electrochemical charge transport and storage. PPY-Graphene 3D composite electrodes prepared by Chabi et al using both chemical and electrochemical deposition [85], showed a high capacity of 660 F g À 1 with an excellent capacity retention of 100% after 6000 cycles. In contrast to the bare PPY electrode, which lost its initial capacitance significantly after few hundreds of charge-discharges due to the mechanical degradation of the electrode materials, both graphene foam (GF) and PPY-GF showed 100% capacitance retention due to the high mechanical strength and flexibility of the GF.…”
Section: D Graphene-based Architectures As Scaffolds In Supercapacitorsmentioning
confidence: 98%
“…23 Recent studies have shown that 3D hierarchical nanostructures were a promising candidate for supercapacitors because these nanoarchitectures can provide continuous electron pathways to ensure good electrical contact and offer shortened diffusion pathways to facilitate ion transport. 24,25 For example, 3D graphene-based electrodes, 26,27 hierarchical porous carbons, 28 and hierarchical hybrid nanostructures, 29 have been developed. Despite these achievements, it is highly desirable to develop simple and scalable methods to synthesize 3D carbon nanostructures with high capacitance and excellent cycling stability for supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene can be a perfect conductive support, or additive for electrode materials with pseudocapacitance properties [17]. Metalic nanoparticles [18], nanostructured oxides [19][20][21] and conducting polymers [22] were coupled with highly conducting graphene nanosheets and reduced graphene oxide to improve performance of Li-ion batteries and supercapacitors.…”
Section: Introductionmentioning
confidence: 99%